Enhancing Student Learning in Mathematics through Numbered Head Together: An Experimental Study - Gigih Kridantari; Budi Usodo; Siswanto Siswanto; Lukman Hakim Muhaimin; Agus Hendriyanto (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
Student problem-solving is fundamental in mathematics because, in problem-solving, students can explore the subject by applying the concepts to real-world problems. NHT is one of the learning models where students can work together to solve problems and an effective method to encourage students to become more involved and think critically. This study aims to determine the effect of the Numbered Heads Together learning model on problem-solving 101 students in class X SMA Negeri Punung in 2022/2023. The research method used is pseudo-experimental research because researchers want to know the effect of the NHT model on student problem-solving. Data analysis using Anava showed that the significance value <0.05. The anava results showed an effect of the learning model on students' problem-solving ability. After further testing, there is a difference in the average value of students subjected to NHT treatment higher than students subjected to TPS and conventional treatment. Based on the study results, the NHT model is more effective in improving students' problem-solving ability in class X SMA Negeri Punung in 2022/2023.